Check list of marine fishes from Simeulue Island waters, Aceh Province, Indonesia - Agung Setia Batubara; Zainal A. Muchlisin; Muhammad Yunus Thamren; Usnardi Usnardi; Nur Fadli (Syiah Kuala University, 2017)
The objective of the present study was to inventory the marine commercial fishes in Simeulue waters, Aceh Province, Indonesia. Sampling was conducted on August 2017. The sampling was conducted in fish landing and direct sampling by using handline hooks and casting net. A total of 77 species of marine commercial fishes belong to 7 orderS, 26 families and 54 genera were recorded during the study. Serranidae was a predominant family with 14 species followed by Lutjanidae with 13 species and Carangidae 9 species